Aktivitas Antibakteri Ekstrak Dan Fraksi Herba Kemangi (Ocimum Sanctum L) Terhadap Staphylococcus Aureus Dan Pseudomonas Aeruginosa - Taufik Turahman; Ghani Nurfiana Fadma Sari (Jurnal Farmasi Indonesia, 2019)
Infectious disease is still one of the public health problems, especially in developing countries. Etiology is generally caused by Staphylococcus aureus and Pseudomonas aeruginosa. Basil (Ocimum sanctum L) is a plant known as lalapan which has antioxidant, anticancer and antimicrobial properties but there is not much scientific information as an antibacterial. This study aims to determine the chemical content and antibacterial activity of ethanol extract, n-hexane fraction, ethyl acetate and basil herb water on the growth of Staphylococcus aureus and Pseudomonas aeruginosa by diffusion and dilution. Herbs are macerated using 96% ethanol. The extract obtained was then suspended with water and then fractionated with n-hexane and ethyl acetate. Basil extract and the fractions obtained were then tested for antibacterial activity at concentrations of 12.5%, 25% and 50% using the diffusion method. The MIC and MBC of the most active fractions can be known using dilution tests with concentrations of 0.78, 1.56, 3.125, 6.25%, 12.5%, 25% and 50%. Ciprofloxacin positive control 5μg/15μl and negative control using sterile 80% 5% tween. Identification of groups of compounds is done by the test tube method. Antibacterial activity test results showed that the zone of inhibition zone in gram-negative bacteria in general tends to be larger than gram-positive bacteria. The largest inhibition zone diameter in the bacterium Pseudomonas aeruginosa in the ethyl acetate fraction basil concentration 50% with a diameter of inhibition zone (10 mm), in the Staphylococcus aureus bacteria found in the ethyl acetate fraction at a concentration of 50% has inhibitory power of (8.6 mm). The results of the identification of the chemical content showed that the extract and fraction of basil herbs contain flavonoids, saponins and steroids and tannins Keywords: Antibacterial, Basil (Ocimum sanctum L), Staphylococcus aureus, Pseudomonas aeruginosa